ANALISIS PENGAKUAN DAN PENGUNGKAPAN PENDAPATAN PADA LAPORAN KEUANGAN PT. ADHI KARYA (Persero Tbk) BERDASARKAN PSAK 23, PSAK 34, PSAK 44 - Hidayat, Muhammad (Universitas Riau Kepulauan, 2016)
The aims of this study is to determine whether the recognition and disclosure of revenues has been applied in accordance with related PSAK to the financial statements of PT.Adhi Karya (Persero Tbk) in 2015. This research uses qualitative descriptive method with comparative analysis. The company's main source of revenue is from the construction activity, but this company also has several other sources of revenue, so that in the application of revenue recognition and revenue disclosure at the financial statement need to pay attention to PSAK 23, PSAK, 34 and PSAK 44. The results showed that the financial statements. Adhi Karya (Persero Tbk) in 2015 has made the recognition and disclosure in accordance with PSAK 23 and PSAK 34. The real estate revenue has been recognized in accordance with PSAK 44 but the disclosure has not been done completely.Keywords: Revenue , Recognition, Disclosure, Construction and Real Estate